Chronic Suppurative Otitis Media (CSOM): Etiological Agents and Antibiotic Sensitivity Pattern of the Isolates (Journal of Medicine, 2015)
Introduction: Chronic suppurative otitis media (CSOM) remains one of the most common childhood chronic infectious diseases worldwide. It is recognized as an important cause of preventable hearing loss in the developing world. The present study was carried out to determine the etiological agent of CSOM and their antibiotic susceptibility pattern at the teaching hospital in North Karnataka.Methods: Samples were collected from patients in accordance with standard protocols. Organisms were identified by conventional microbiological techniques. Antibiotic susceptibility of the isolates was done by disc diffusion method according Clinical Laboratory Standards Institute (CLSI) guidelines.Results: A total of 159 patients were included in the study, out of which 53.5 % were males. Majority of the patients (85/159) were in the age group of 1-20 years. Pseudomonas was the most common organism causing CSOM, closely followed by Staphylococcus aureus. Pseudomonas were more sensitive to piperacilln-tazobactam (91%), followed by amikacin (80%). Among Staphylococcal isolates sensitivity was more to linezolid (93%), closely followed by piperacilln -tazobactam (88%). 73% of the Gram negative bacilli were sensitive to amikacin and 67% to gentamicinConclusion: Due to the easy availability and widespread use of antibiotics the susceptibility pattern of the pathogenic microorganisms are changing, therefore it is imperative to know the local susceptibility pattern of the causative agents, to treat the infection effectively.J MEDICINE July 2015; 16 (2) : 79-82